Microstructure based finite element analysis for deformation behavior of magnesium based composites - Prasanth Kumar, B. (Asian Research Publishing Network, 2016)
In Metal matrix composites (MMC) the microstructural aspects such as reinforcement size, shape and distribution plays important role in the deformation behaviour of composites. To study the thermal and structural deformation behaviour of real microstructure, an analytical approach was proposed by developing a two dimensional (2D) model from a microstructure image of magnesium hybrid composites and magnesium CNT composites. Samples of both magnesium hybrid (1CNT, 2 silicon carbide) and magnesium mono composite (1CNT) were fabricated using stir casting method. The microstructure images of samples were converted into equivalent CAD format using canny edge detection method. In the present work the deformation behaviour such as the thermal stress and strain and structural analysis were studied by using finite element analysis. Experimental tensile testing of magnesium hybrid composites was also conducted. Â© 2006-2016 Asian Research Publishing Network (ARPN).